Efeito da adição de lama vermelha como carga nas propriedades mecânicas de compósitos de poliéster insaturado reforçado com fibra natural de curauá (Ananas erectifolius) - OLIVEIRA, Mauro Júnior Aires de (Universidade Federal do Pará, 2014)
Nowadays, due to the increasing need for good mechanical performance and due to the environmental issues, researchers have tried to replace synthetic fibers used in composites (such as glass fiber) for natural fibers. A natural fiber that has already been used in the automobile industry is the curaua fiber (Ananas erectifolius) which shows excellent tensile strength. Expecting to enhance some properties of the composites and to minimize the usage of resin, and this way minimize costs, it has been researched the utilization of fillers incorporated to composites matrices. In recent papers, it has been studied the utilization of red mud (waste of the bauxite industry) as filler due to the great availability, low cost and for being potentially dangerous to the environment. The objective of this work was to evaluate effects of red mud addition on the mechanical properties of Curaua fiber (Ananas erectifolius) reinforced composites. The results showed that the using of red mud as filler in volume fractions equal or higher than 20% and Curaua fiber in volume fraction of 5% was improved significantly the reinforcing effect.